Comparative Efficacy of Dapagliflozin and Empagliflozin of a Fixed Dose in Heart Failure: A Network Meta-Analysis - Shi, Zepeng; Gao, Feng; Liu, Wei; He, Xuezhi (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: The efficacy of dapagliflozin and empagliflozin in Sodium-glucose Cotransport-2 Inhibitors (SGLT-2i) in patients with heart failure (HF) has been discovered. However which drug could improve varied prognostic outcomes have not been elucidated. Hence, we compared the efficacy of them on prognostic improvement of HF. Methods: Databases including PubMed, EMBASE, Scopus, Google scholars, and the Cochrane Library were searched for all related randomized controlled trials (RCTs) published from inception to 13th October 2021. Network meta-analyses were performed to generate matrices to show the effect size for pairwise comparison regarding to all interventions. Results: Eventually a total of 11 RCTs were included in this study. For the primary endpoints, dapagliflozin was comparable with empagliflozin in hospitalization for HF, and empagliflozin (OR=0.70, 95%CI: 0.59-0.84) decreased the risk of exacerbation of HF over dapagliflozin. For the secondary endpoints, dapagliflozin was comparable with empagliflozin in cardiovascular (CV) death / hospitalization for HF, and for CV death, dapagliflozin (OR=0.78, 95%CI: 0.65-0.92) significantly reduced mortality over placebo. For the tertiary endpoints, dapagliflozin (OR=0.80, 95%CI: 0.66-0.98) significantly decreased the mortality over empagliflozin in all-cause death, and neither drug significantly increased the risk of hypoglycemia. Recommendations: Overall, 10mg/day dapagliflozin may be the optimal recommendation for its premium and comprehensive effect on improving the prognosis of patients with HF compared to 10mg/day empagliflozin.